"There’d always be something left" : (im)matérialité de la ville dans Hughie de Eugene O’Neill - Aurélie Sanchez (Anglophonia)
Eugene O’Neill’s Hughie exemplifies the dramatist’s concern with the theme of absence. In this late one-act play, New York remains at first invisible and the stage constitutes an empty space. The city is characterized by emptiness and anonymity. The scenery of the play only emphasizes the vacuity of the two characters’ existence. Yet the city eventually asserts itself on stage through the long, elegiac monologue of Erie Smith, a gambler mourning for a deceased night clerk. His vivid depiction of Broadway evokes a long-lost urban lifestyle. New York is also brought to life thanks to a series of echoes and sounds that reverberate on stage and draw the characters’ attention on the off-stage. Language and specifically rumours appear as both destroying forces and life-giving sources of illusion.